2018
DOI: 10.1007/s00167-018-5179-9
|View full text |Cite
|
Sign up to set email alerts
|

Excellent 10-year patient-reported outcomes and survival in a single-radius, cruciate-retaining total knee arthroplasty

Abstract: PurposeOver 2 million Triathlon single-radius total knee arthroplasties (TKAs) have been implanted worldwide. This study reports the 10-year survival and patient-reported outcome of the Triathlon TKA in a single independent centre.MethodsFrom 2006 to 2007, 462 consecutive cruciate-retaining Triathlon TKAs were implanted in 426 patients (median age 69 (21–89), 289 (62.5%) female). Patellae were not routinely resurfaced. Patient-reported outcome measures (SF-12, Oxford Knee Scores (OKS), satisfaction) were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…Those who became less fulfilled (58%) experienced a decline in OKS over this time period. Previous 10-year follow-up studies of TKA have shown a mean decline in both knee-specific function scores and the physical component element of generic health scores from 5 to 10 years [25]. This is consistent with patient aging and is not a surprising trend.…”
Section: Percentage Of Pa Ents Sta Ng This Expecta On Was Important Psupporting
confidence: 78%
“…Those who became less fulfilled (58%) experienced a decline in OKS over this time period. Previous 10-year follow-up studies of TKA have shown a mean decline in both knee-specific function scores and the physical component element of generic health scores from 5 to 10 years [25]. This is consistent with patient aging and is not a surprising trend.…”
Section: Percentage Of Pa Ents Sta Ng This Expecta On Was Important Psupporting
confidence: 78%
“…1 ). The TKAs were performed by 7 surgeons at a large orthopaedic teaching hospital 9 . At 10 years, 326 patients were alive with an intact TKA.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who did not respond by mail were telephoned. Full details and analysis of the entire cohort (n = 462) have been published previously 9 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is limited in that 33% of patients were lost to follow up. This was significantly higher than studies of similar length follow up [7] likely due to the high propensity of retirees in the area to relocate secondary to the cost of living in this particular geographic region. Recent studies show that from 2010-2017, New York State experienced negative net domestic migration of over 1 million persons.…”
Section: Discussionmentioning
confidence: 69%